PENGARUH MANAJEMEN KELAS TERHADAP KEMANDIRIAN BELAJAR DAN SEMANGAT BELAJAR SISWA - Nova Ida Silalahi (STKIP Pesisir Selatan, 2026)
This study aims to examine the effect of classroom management on students’ self-regulated learning and learning enthusiasm at SMP Nommensen Jambi. The study is motivated by the relatively low level of students’ learning independence and fluctuating learning motivation in classroom activities. Classroom management plays a strategic role in creating a conducive learning environment that supports students’ behavioral development. This research employed a quantitative approach with an associative design. The population consisted of all students, with a total sample of 85 students selected using total sampling. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using SPSS and SmartPLS through measurement and structural model evaluation. The results indicate that classroom management has a positive and significant effect on self-regulated learning (β = 0.728; p < 0.05) and learning enthusiasm (β = 0.701; p < 0.05). These findings confirm that effective classroom management enhances students’ independence and motivation in learning. This study highlights the importance of classroom management in improving the quality of learning processes.